COMPARATIVE EFFICACY OF YUCCA SCHIDIGERA EXTRACT AND FRUSEMIDE IN ASCITES OF BROILER CHICKS, UNDER FIELD CONDITIONS - Ejaz, Sohail; Ashraf, Muhammad; Khan, Muhammad Athar; Rabbani, Masood (Journal of Research (Science), 2004)
Ascites is a condition with excess amount of ascitic fluid in the abdominal cavity. This study was conducted to evaluate the comparative efficacy of “Yucca schidigera” extract and “frusemide” in ascites of broiler chicks. Fifty broiler flocks affected from ascites were selected. From each broiler flock, one hundred and fifty birds were randomly selected and were divided into three groups A, B and C containing fifty birds in each group. The chicks of group “A” were given “Yucca schidigera” extract (1ml per 20L) and chicks of group “B” were given “frusemide” (1gm per liter), in drinking water for three days, while chicks of group “C” served as control. Feed intake, water intake, weight gain and reduction in amount of ascitic fluid were recorded before and after the treatment. “Yucca schidigera” treated birds gave better performance than “frusemide” treated as well as “control” group. From this study, it maybe concluded that the use of “Yucca schidigera” extract in ascites of broiler chicks is a better choice than frusemide.